Mapping of the Creative Industries of the Used Rubber Crafts Sector Using Geographic Information Systems Against the Economic Impact of the Community With Productivity Measurements - Oktalia Triananda Lovita; Meraty Ramadhini (Jurnal Inotera, 2019)
The handicraft industry is one of the industrial sectors that provides a major contribution to the community's economy. Creative industries have 14 sectors according to the provisions of the KBLI (Indonesian Business Field Book Classification). This research was conducted in the Kluet Sub-district of South Aceh by mapping the creative industries in the Kluet Sub-district of South Aceh on the economic impact of the community which is influenced by 4 indicators namely labor, capital, total production and income. South Aceh Kluet Subdistrict is dominated by one sector, namely the Used Tires Rubber craft sector. To determine the development and influence of the creative industry on the economy, productivity is measured by making a ratio between effectiveness (output) and efficiency (input). The results of the assessment of each indicator by comparing 2018 and 2019. There is an increase from the previous year, meaning that the greater the value of productivity, the better the achievement target. Productivity measurement of the results obtained is based on labor indicators in 2018 obtained capital value in 2018 gained Rp1.4 and in 2019 amounted to Rp 1.9. There is an increase from the previous year, meaning that the greater the value of productivity, the better the achievement target. Productivity measurement results obtained are based on labor indicators in 2018 obtained productivity values ​​of 3 units / person in 2019 amounted to 5 units / person, the above results show an increase from 2018 to 2019. This means that the effectiveness of achieving quality levels of efficient use of resources has increased. The results above indicate an increase from 2018 to 2019. This means that the effectiveness of achieving the quality level of the efficient use of resources has increased.